Media Pembelajaran Peralatan Servis Sepeda Motor dengan Menerapkan Teknologi Augmented Reality - Miftahul Madani; Melati Rosanensi (Sekawan Institut, 2025)
Learning media is one of the key components in the educational process. Teachers need to pay special attention to the use of learning media during teaching and learning activities. However, a lack of variety and suboptimal utilization of learning media often causes students to lose interest in learning. In fact, learning media aim to serve as tools to enhance the effectiveness of the learning process. Learning media are available in various forms, one of which is printed media or verbal explanation-based methods that are widely used in schools. This type of media is chosen for its practicality, adaptability to students' abilities, and ease of distribution. However, printed media have limitations, such as the inability to present elements like sound, animation, or three-dimensional objects. This study employs the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: Concept, Design, Material Collection, Assembly, Testing, and Distribution. The final product of this research is an application in